The "face" of coach development: a systematic review of the role of the coach developer - Jones, T.; Allen, J.; Macdonald, S. (International Sport Coaching Journal, 2024)
The purpose of this paper was to systematically review the peer-reviewed literature on the role of the coach developer (CD). Three questions guided this review: (a) who is the CD, (b) what do they do, and (c) how do they do it? Using five electronic databases—SPORTDiscus, ERIC, PsycInfo, Web of Science, and Scopus—a total of 595 articles were initially found with 42 identified as appropriate for inclusion following PRISMA guidelines. A further 11 were added, via the screening of reference lists and during the process of writing, to total 53 articles. Data analysis comprised of content analysis to describe and identify gaps in the research, and reflexive thematic analysis to facilitate the analysis of the findings from the included studies. Content analysis findings show an increase in researching this role and a breadth of methodology and theoretical frameworks being employed. Utilising reflexive thematic analysis, seven themes were generated to understand the who, what, and how of the CD. Findings suggest a diverse and contextualised appreciation of the various roles the CD undertakes as encompassed by the International Council for Coaching Excellence (ICCE) umbrella term definition. The discussion reveals the complexity of the role as CDs navigate who they are, what they do, and how they do it. Recommendations are made for future research to mediate knowledge gaps and move towards alignment and understanding of this key figure.